2017
DOI: 10.1016/j.actamat.2017.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural evolution of single Ni2TiAl or hierarchical NiAl/Ni2TiAl precipitates in Fe-Ni-Al-Cr-Ti ferritic alloys during thermal treatment for elevated-temperature applications

Abstract: Precipitate features, such as the size, morphology, and distribution, are important parameters determining the mechanical properties of semi-or fully-coherent precipitatehardened alloys at elevated temperatures. In this study, the microstructural formation and evolution of recently-developed Fe-Ni-Al-Cr-Ti alloys with superior creep resistance have been systematically investigated using transmission-electron microscopy (TEM), scanning-electron microscopy (SEM), and atom-probe tomography (APT). These alloys wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 63 publications
0
29
0
Order By: Relevance
“…Both alloys often contain a small Fe inclusion within the precipitates, which was previously determined by energy-dispersive X-ray spectroscopy1819. It was suggested that the hierarchical precipitate structure is effective to retain the coherent interface, whereas the single Ni 2 TiAl precipitate tends to form misfit dislocation at the interface in order to accommodate the large lattice mismatch1820.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Both alloys often contain a small Fe inclusion within the precipitates, which was previously determined by energy-dispersive X-ray spectroscopy1819. It was suggested that the hierarchical precipitate structure is effective to retain the coherent interface, whereas the single Ni 2 TiAl precipitate tends to form misfit dislocation at the interface in order to accommodate the large lattice mismatch1820.…”
mentioning
confidence: 96%
“…The microstructures of the alloys, such as chemistry and morphology of the constitutive phases within the precipitates, have been systematically characterized using transmission-electron microscopy (TEM) and atom-probe tomography (APT)181920. The microstructural features of the 4-wt.% and 2-wt.%-Ti alloys aged at 973 K for 100 hours are displayed in Fig.…”
mentioning
confidence: 99%
“…It has been demonstrated that the coherent strengthening of cuboidal B2-AlNi or L2 1 -Ni 2 AlTi nanoprecipitates in the BCC matrix can improve mechanical property of alloys on a large extent. 23,35,38 Comparing the T1 with the T2 containing similar microstructure but different Ti contents, the latter T2 HEA exhibits a relatively higher strength (1826 6 42 MPa) than the former T1 (1791 6 18 MPa), which might be caused by the smaller particle size of L2 1 nanoprecipitates. Further increasing the Ti content up to 6.25 at.% in the T3 alloy with an Al/Ti ratio of 1/1, the alloy is brittle and the fracture happens before yielding, which is caused by the brittle r matrix.…”
Section: A Microstructural Characteristicsmentioning
confidence: 99%
“…32,33 Intriguingly, further addition of 2 wt% Ti into FBB8 renders the alloy with cuboidal L2 1 /B2 hierarchical nanoprecipitates, resulting in a significant improvement of the creep-resistant property at a HT of 700°C. [33][34][35][36] In addition, cuboidal L2 1 nanoparticles were also precipitated in a newly designed light-weight BCC-based Al 1.5 CrFeMnTi HEA, which exhibits a high microstructural stability. 37 In our recent work, we designed a series of HEAs 23,38 with a composition of Al 2 M 14 (M represents different combinations of Ni, Co, Fe, and Cr) with the guide of the cluster formula approach, 39 in which the cuboidal B2 nanoparticles are found to be precipitated coherently into the BCC matrix.…”
Section: Introductionmentioning
confidence: 99%
“…%)] [25][26][27][28]. More recently, the coarsening behavior of HPSFA has been systematically studied during long-term thermal treatment at 973 K up to 500 hours, which reveals the duplex precipitates, such as, the primary and secondary, and the morphological transition of the hierarchical precipitates, which is associated with the elastic coherency of the interface between the primary precipitate and matrix [29]. However, a detailed microstructural characterization of the precipitates is necessary to elucidate the creep mechanism(s) and to achieve the further optimization of the creep properties.…”
Section: Introductionmentioning
confidence: 99%